Climate Protection Policy with China and the USA after 2012: Cost Reduction through Emissions Trading and Technological Cooperation - Claudia Kemfert (Weekly Report, 2005)
Greenhouse gas emissions should be stabilized to today's level to prevent harmful climate damage.The countries that have signed the Kyoto Protocol committed themselves to reduce their greenhouse gas emissions over the period 2008 to 2012, but only to a very limited extent. The USA decided not to ratify the Kyoto Protocol for various reasons. Furthermore, fast-growing economies like China are about to catch up with the USA in terms of their energy consumption and gas emissions. Therefore, in the near future it is going to be essential to try and persuade both nations, the USA and China, to accept binding greenhouse gas emission reduction targets. The USA and China need to be convinced to enter a 'Kyoto Plus' Agreement after 2012. In this respect, a clearly defined international trade in emission rights can play an important role. In the industrialized countries, costs of approx. 500 billion US dollars could be avoided until 2050 as compared with a scenario in which there is no emissions trading. In order to lower expenses to this extent, Europe, the USA, Japan and Russia need to reduce their emissions by 3% per year from 2012 onwards as compared with an estimated emission curve according to a 'business as usual' scenario, and moreover, simultaneously China needs to be granted emissions rights after 2012. On the one hand, this would help industrialized countries like the USA to effectively reduce emission reductions costs. On the other hand, China could benefit to a large extent from selling emission rights. Moreover, additional incentives to meet climate protection targets could be created through specific cooperation when investing in new technologies.
Keywords: 330